PROSES BERPIKIR SISWA SMK DENGAN KECERDASAN MUSIKAL DAN KINESTETIK DALAM MEMECAHKAN MASALAH MATEMATIKA - Hermiyati, Yosepha Endang (JSTT, 2015)
This study is a qualitative study aimed to obtain a description of the process of thinking vocational students with musical intelligence and kinesthetic, within solving mathematical problems based on Polya rules. The results of this study were: a) at the time to understand the math problems first by repeated readings, accompanied by movements of the body and / or play objects; b) at the time of plan problem solving, each just used plan a strategy, subjects with musical intelligence was relatively more patient witin finding the idea of solving than subjects with kinesthetic intelligence; c) when implementing the plan problem solving, each using the solving steps according to plan, subject to the musical intelligence to do it relatively more thorough and careful than subjects with kinesthetic intelligence; d) at the time of re-examine the results of its work, each recheck before finally, but the subject of the musical intelligence to re-examine the results of his work after until final.